Efektivitas dan Hambatan dalam Pengadaan Tanah untuk Aset yang Disengketakan: Studi Kasus pada PT Pelindo Regional 4 Makassar - Pananrang, Akbar Tenritetta (Sovereign: International Journal of Law, 2024)
This study aims to analyze the effectiveness of implementing land acquisition for public interest involving disputed assets at PT Pelindo Regional 4 Makassar, as well as the factors influencing said effectiveness. Employing a quantitative descriptive approach, this research utilized both normative and empirical legal methodologies. The study was conducted in Makassar City. Data collection techniques included questionnaires, documentation, and literature study. The collected data were analyzed using quantitative data analysis techniques and presented through frequency distribution tables. Research findings indicate that the land acquisition for public interest involving disputed assets at PT Pelindo Regional 4 Makassar has been carried out in accordance with applicable laws and regulations. However, its implementation has not achieved full effectiveness, particularly concerning the following activities: the inventory and identification of land tenure, ownership, use, and utilization; compensation assessment; compensation disbursement; and land relinquishment. Furthermore, four factors were found to influence the effectiveness of implementing this land acquisition: legal substance, legal culture, facilities and infrastructure, and community legal awareness.